Measuring The Infiltration Rate Of Biopore Holes Using Selection And Composittion Of Wase ( A Case Study Conducted At Campus 1 Of Ukrida Jakarta) - Sanjaya, William; Christian, Kevin Billy; Gunaran, Danny; Budirahardjo, Elly Kusumawati (Teknik dan Ilmu Komputer, 2017)
AbstractÃÂ Biopore,a water conservation technique, are holes made on the earths surface that function as the entrance for rainwater into the soil. This research aims to determine the infiltration rate of biopore holes in various waste to further analyze the waste composition that affects the rate the most. Each hole infiltration rate is tested every week for 10 weeks. The result shows connection between the waste type and composition and the age of the waste. The waste used are dry leaves, meat or fish waste, and organic kitchen waste. Wet waste tends to increase the infiltrationÃÂ rate (98.365%) greater than dry waste (58.06%). Meat or fish waste needs more time (four weeks) to reach maximum increase rate comparedÃÂ to the other types of waste. In addition, the dominant composition of wet waste in the mixture has increased the infiltration rate. The maximum infiltration rate of biopore holes is reached between the second week and the fourth week. The surrounding environmment such as weather and soil charateristics can affect the acquired data.ÃÂ Keywords: biopore, infiltration rate, organic waste